2023
DOI: 10.1177/10998004231218887
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Family-Based Diabetes Management Intervention on Glycated Haemoglobin Among Adults With Type 2 Diabetes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Margareta Teli,
Ratsiri Thato,
Faizul Hasan
et al.

Abstract: Background: Glycated hemoglobin (HbA1c) control is a crucial goal in the management of type 2 diabetes mellitus (T2DM), requiring lifelong commitment and family support. This study aimed to assess the effectiveness of family-based diabetes management intervention on HbA1c among adults with T2DM. Methods: From inception up to 2022, a comprehensive literature search was conducted across PubMed, ProQuest, Scopus, CORE, and the Cochrane Library. The quality of studies was evaluated using the Joanna Briggs Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…Comparing these two studies in Indigenous populations in North American, the dilemma of study heterogeneity reported by Baig et al ( 17 ) becomes clear. A more recent review of family-based randomized control trials among adults with type 2 diabetes showed moderate heterogeneity across trials ( n = 18) and reported similar issues related to variable family involvement across trials ( 19 ). However, results did show significant improvements in A1c levels with greater improvements in developing areas compared to developed countries ( 19 ).…”
Section: Integral Medicine Wheel Domains Of Health To Explorementioning
confidence: 99%
“…Comparing these two studies in Indigenous populations in North American, the dilemma of study heterogeneity reported by Baig et al ( 17 ) becomes clear. A more recent review of family-based randomized control trials among adults with type 2 diabetes showed moderate heterogeneity across trials ( n = 18) and reported similar issues related to variable family involvement across trials ( 19 ). However, results did show significant improvements in A1c levels with greater improvements in developing areas compared to developed countries ( 19 ).…”
Section: Integral Medicine Wheel Domains Of Health To Explorementioning
confidence: 99%
“…Specifically, peer support provided in small group settings, short-term interventions, and weekly meetings may yield more favorable outcomes[ 120 ]. Empirical studies of peer support programs indicate that prolonged participation in peer support is beneficial for reducing A1C levels and improving QoL[ 121 ] and distress[ 122 ], especially among individuals with a lower socioeconomic status[ 120 , 123 - 125 ]. Additionally, volunteers who serve as peer supporters (those who themselves have diabetes) may achieve better health outcomes due to their involvement in relevant activities[ 126 ].…”
Section: Introductionmentioning
confidence: 99%